2014
DOI: 10.7567/jjap.53.11ra10
|View full text |Cite
|
Sign up to set email alerts
|

Properties of p-type N-doped Cu2O thin films prepared by reactive sputtering

Abstract: We have investigated the electrical, optical, and structural properties of p-type nitrogen (N)-doped Cu 2 O thin films prepared at various nitrogen gas flow rates for application in heterojunction solar cells. The N-doped Cu 2 O thin films were fabricated by facing-target reactive sputtering. The hole concentration of the N-doped Cu 2 O thin films was affected by N 2 gas flow rate. With increasing N 2 gas flow rate from 0 to 0.5 sccm, the hole concentration and mobility of N-doped Cu 2 O films increased sharpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…17,18 Many efforts have been made, both theoretically and experimentally, to address the influence of incorporation of N dopants in Cu 2 O. [19][20][21][22][23][24][25] It has been also shown that the structural, electrical, and optical properties of Cu 2 O are strongly influenced by N incorporation. 22 However, despite the higher predicated theoretical conversion efficiency than Cu 2 O, no comprehensive investigation has yet been conducted to address the influence of N incorporation in CuO.…”
Section: Optical Bandgap Widening and Phase Transformation Of Nitroge...mentioning
confidence: 99%
“…Paper VI and Refs. 76,95,166), but most reported as-deposited Cu 2 O thin film mobilities are below 10 cm 2 /Vs [80,82,83,[167][168][169][170][171][172]. A common way of improving the electrical, optical and structural characteristics of semiconductors is through heat treatment, since the excess energy provided to the lattice annihilates point and extended defects, improves the crystallinity, and reduces In Paper VII, reactively RF sputtered Cu 2 O thin films are RTA treated at 600 • C, 700 • C, 800 • C, and 900 • C for 3 min in a p O 2 of 10 Pa, and subsequently, their structural, optical, and electrical properties are probed by XRD, Scanning Electron Microscopy (SEM), UV-VIS spectroscopy, PL spectroscopy and Hall effect measurements.…”
Section: Homoepitaxial Growth Of Zno By Rf-magnetron Sputteringmentioning
confidence: 99%